Functional polymorphisms of the APOA1/C3/A4/A5-ZPR1-BUD13 gene cluster are associated with dyslipidemia in a sex-specific pattern - Wei Bai; Changgui Kou; Lili Zhang; Yueyue You; Weiying Yu; Wanqing Hua; Yuanyuan Li; Yaqin Yu; Tiancheng Zhao; Yanhua Wu (PeerJ, 2019)
Background Dyslipidemia contributes to the risk of many diseases, including stroke, cardiovascular disease and metabolic-related diseases. Previous studies have indicated that single nucleotide polymorphisms (SNPs) are associated with different levels of serum lipid. Therefore, this study explored the relationship between the APOA1/C3/A4/A5-ZPR1-BUD13 gene cluster gene polymorphisms and dyslipidemia in the total sample population and stratified by genders in a northeast Chinese population. Methods A total of 3,850 participants from Jilin Province, China, were enrolled in our study, and their serum lipid levels were measured. Six functional SNPs (APOA1 rs5072, APOC3 rs5128, APOA4 rs5104, APOA5 rs651821, ZPR1 rs2075294 and BUD13 rs10488698) were genotyped using polymerase chain reaction and MALDI-TOF-MS. Logistic regression analysis was performed to explore the relationship of APOA1/C3/A4/A5-ZPR1-BUD13 gene cluster gene polymorphisms with dyslipidemia. Linkage disequilibrium and haplotype analyses were performed with the SNPStats program and Haploview software. Results All SNPs conformed to Hardy–Weinberg equilibrium. Logistic regression analysis revealed that rs5072, rs5128 and rs651821 were associated with hypertriglyceridemia, rs5104 and rs651821 were associated with low-HDL cholesterolemia in overall group. rs651821 was associated with hypertriglyceridemia and low-HDL cholesterolemia in both the male and female group. However, among females, rs5072 was observed to be associated with hypertriglyceridemia. Haplotype analysis showed that haplotypes TGCCGC and CAGCGC were associated with dyslipidemia in the overall, male and female groups. Conclusion SNPs in the APOA1/C3/A4/A5-ZPR1-BUD13 gene cluster were associated with dyslipidemia. Furthermore, the association of APOA1 rs5072 in this gene cluster with dyslipidemia differed between genders; thus, additional studies are needed to confirm this conclusion, and the mechanisms underlying these results warrant further exploration.